APLIKASI JASA PERTUKANGAN DI WILAYAH KUALA TUNGKAL JAMBI: Booking;Builder;Service;Society;System. - Limia Budiarti, Rike; Permata Ananda, Selvi (JURNAL AKADEMIKA, 2021)
A handyman has many benefits, one of which is an element of aesthetics or beauty in building or renovating a house. In addition to having an aesthetic element, a professional handyman also has a high selling point because not everyone can do it. The things that are considered by the community in choosing a handyman are certain what skills the craftsman has, how is the quality of his work and how much is the wages for using his services. Oftentimes, the builders we find cannot do the work we offer for several reasons. Therefore, one of the important things that must be done to make it easier for the community and craftsmen in the Kuala Tungkal area is to provide a means of finding information about good carpentry services. Through this system, the community and expert craftsmen in the Kuala Tungkal area can easily exchange information and negotiate without having to meet in person.